Outcome of Tympanoplasty with and without Cortical Mastoidectomy for Tubotympanic Chronic Otitis Media. (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):478-483 The abstract of this article is available on the PubMed website